Eco-Social Strengthening, Assertive, and Effective Communication, in Gen Z Poverty Alleviation at The JPC Foundation Through The RPJ: - - Erlina Puspitaloka Mahadewi; Mohamad Reza Hilmy; Intan Silviana Mustikawati; Samudro Seto; Ayu Larasati; Arnastya Iswara Sanantagraha (CV. Inara, 2026)
This study aims to capture the patterns of economic strengthening of the people of Jakarta, especially Central Jakarta, around the JPC foundation office in Indonesia. In order to alleviate poverty due to economic and social aspects, and through an approach by engaging the community and related communities, to synergize in achieving goals. The method used in this writing is a descriptive method. While the design used in this writing is a library studies design, where the author conducts a search for literature and then conducts a review. The synergy of poverty alleviation strategies has been formulated into five categories, namely: (1) institutional aspects of poverty alleviation; (2) policies and budgeting of programs for poverty alleviation; (3) human resources (4) data and information regarding poverty, and (5) monitoring and evaluation (monev) systems for poverty alleviation policies and programs. Implications are a form of mapping the synergy of poverty alleviation with patterns that involve the community and communities, so that goals can be achieved in a structured and systematic manner, especially for Generation Z.